AI-Enabled Smart Jacket : Revolutionizing Healthcare Monitoring and Environmental Control - M. Harini,; K. S. Roshni,; R. Nega,; Dr. D. Nithya, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The AI smart jacket represents a groundbreaking innovation in healthcare monitoring, merging wearable technology, advanced sensors, and machine learning algorithms. This wearable device integrates GPS and biometric sensors for real-time data capture, facilitating remote access to health metrics via wireless networking. With a focus on user comfort and privacy, the jacket features machine-washable fabrics and robust security measures. Its array of functionalities includes temperature adjustment, SOS capability, oximeter, ECG monitoring, pulse rate tracking, and a fan with massage functions. The jacket's versatility extends from chronic illness management to elderly care, promising to enhance overall well-being and quality of life. By seamlessly integrating technology into daily life, the AI smart jacket stands as a pioneering solution at the forefront of healthcare innovation.
Keywords: AI; Smart Jacket; Healthcare Monitoring; Environmental Control; Deep Q-Learning; Deep Belief Networks; Wearable Technology